Fire plus hazardous gas detection system with an sms alert . - Mungwariri, Munashe Delight (Midlands State University, 2020)
The study was carried out to design and implement a fire plus hazardous gas detection system as a measure to curb the destruction of properties and lives in homes and industries. The system includes various functionalities that make it suitable for use in a country like Zimbabwe where a number of properties have been lost due to fires and a lot of these fires have started due to gas leakage. The inhalation of Liquid Petroleum Gas in excess is really a burden as this causes an increase in the number of deaths per year by deteriorating health. In the compilation process, the major idea used was to put together sensors (flame, gas), wires, liquid crystal display, global system for mobile communications modem and other necessary components to function as one entity with the sole purpose of detecting gas and fire and also put measures to deal with them. The first functionality of the system was to detect fire using a flame sensor and this would activate the sprinkler to sprinkle water on the affected area to reduce the effect of the fire as well as sending a message through a global system for mobile communications modem and sounding a buzzer. The other functionality is to detect gas then it activates a cooling fan as well as sending a message to the directed destination and sounding a buzzer to alert of the danger. To reduce the concentration of the gas that would have leaked, a cooling fan is used to provide fresh air in the process. An MQ2 gas sensor was used to detect gas and on testing the system it gave adequate information and timely alert as messages on detecting the gas leakage. The use of the liquid crystal display was to display the values of the gas and fire. It also displayed a notification that gas or fire had been detected and if a message had been sent to the authorized phone number. For future development, it was recommended to implement a system which has sensors that sense the direction where the heat is coming from such that when fire is detected a sprinkler points and sprinkles the water in the right direction. It was also recommended to make use of a number of high quality flame and gas sensors.